Description and evaluation of the Earth System Regional Climate Model (Reg CM‐ES). (8th August 2017) - Sitz, L. E.; Di Sante, F.; Farneti, R.; Fuentes‐Franco, R.; Coppola, E.; Mariotti, L.; Reale, M.; Sannino, G.; Barreiro, M.; Nogherotto, R.; Giuliani, G.; Graffino, G.; et al.
Abstract: We describe a new, state‐of‐the‐art, Earth System Regional Climate Model (RegCM‐ES), which includes the coupling between the atmosphere, ocean, and land surface, as well as a hydrological and ocean biogeochemistry model, with the capability of using a variety of physical parameterizations. The regional coupled model has been implemented and tested over some of the COordinated Regional climate Downscaling Experiment (CORDEX) domains and more regional settings featuring climatically important coupled phenomena. Regional coupled ocean‐atmosphere models can be especially useful tools to provide information on the mechanisms of air‐sea interactions and feedbacks occurring at fine spatial and temporal scales. RegCM‐ES shows a good representation of precipitation and SST fields over the domains tested, as well as realistic simulations of coupled air‐sea processes and interactions. The RegCM‐ES model, which can be easily implemented over any regional domain of interest, is open source, making it suitable for usage by the broad scientific community. Plain Language Summary: The increasing availability of observational data sets of high temporal and spatial resolution is providing a more complete view of the ocean and atmosphere, revealing strong air‐sea coupling processes. In order to obtain an accurate representation and better understanding of the climate system, its variability, and possible future change, the inclusion of all mechanisms of interaction among the different climate components becomes ever more desirable. Regional coupled ocean‐atmosphere models can be especially useful tools to provide information on the mechanisms of air‐sea interactions and feedback occurring at regional fine spatial and temporal scales. Here we present a new, state‐of‐the‐art, Earth System Regional Climate Model (RegCM‐ES). Key Points: A new Regional Earth System Model (RegCM‐ES) successfully simulates climate features in regions where coupled air‐sea processes are important RegCM‐ES shows reduction of precipitation biases and good performance simulating the effects of air‐sea interactions over frontal regions RegCM‐ES is an open source community model, making it suitable for use by a large scientific community on any regional domain of interest